What characteristics of technology and its vendor encourage continuous usage intention of accounting software in SMEs? - Uddin, Md. Minhaj; Hossain, Md. Alamgir; Pias, Mahmudul Hasan (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
The purpose of this study was to identify the technology related factors (accounting software) and its suppliers that influence SME owners or managers to adopt and continue using accounting software. Using a convenience sampling technique, data were collected from 356 respondents who worked as the owner or manager of SMEs in Bangladesh. Partial Least Square (PLS) method with Structural Equation Modeling (SEM) was used to analyze the data, and SPSS 24.0 and Smart PLS 3.0 software were used. It was revealed that perceived usefulness, technological characteristics (functionality, timeliness, security and safety) and software vendor related factors (reputation of vendor, regular after sales service, quality support services) drove the users of accounting software in SMEs to continue usage of the software. The study also found that the perceived ease of use and the software price did not influence the behavioural intention of managers to use accounting software. Through identifying the factors driving the behavioural intention of users for selecting the best accounting software, the study is likely to contribute to the decision makers (SMEs owners/managers), software providers, and marketers in information technology (IT) filed in emerging nations like Bangladesh and other nations with a similar context.